Real rigidities, firm dynamics, and monetary nonneutrality: The role of demand shocks - S. Boraægan Aruoba; Eugene Oue; Felipe Saffie; Jonathan L. Willis (Federal Reserve Bank of Atlanta, 2023)
We propose a parsimonious framework for real rigidities, in the form of strategic complementarities, that can generate real and nominal dynamics and match key features of the data across several literatures. Existing menu-cost models featuring strategic complementarities require unrealistically volatile shocks to idiosyncratic productivity to be consistent with pricing moments. We develop a simple menu-cost model with strategic complementarities along with idiosyncratic productivity and demand shocks that are disciplined by the data. This approach allows us to overcome previous criticism from analysis of models that employ only an idiosyncratic productivity shock and calibrate solely using data from the price-adjustment literature. Despite its simplicity, the model can generate sizable monetary nonneutrality along with the magnitude of cost pass-through documented in previous studies, while also remaining consistent with micro pricing and markup evidence.
Keywords: D02; E02; E44; G21; 330; menu costs; strategic complementarities; demand shocks; sticky prices; monetary nonneutrality